Involvement in youth program: what are the major determinants / Norudin Mansor … [et al.] - Mansor, Norudin; Ahmad Hawari, Nur Shazleen Yazmeen; Azmi, Nurul Hafiza; Jaffar, Sarah Hanim (2008)
Over the last decade we have witnessed the soaring number of social problems among the youth in the nation. In addressing the issue, the government has taken the initiative to organize various forms of Youth Programs. Thus, this paper attempts to explore the issues that will influence teenagers' involvement in Youth Programs. The exploration of the study referring to selected identifiable variables related to the social problem, lifestyle, self-development, economic and government policy is useful as a framework for profiling the teenagers' involvement towards Youth Program. Using data that were cross-sectionally examined, this paper seeks to investigate factors that influence teenagers to involve in Youth Program. Focusing on the districts of Marang and Dungun, 262 samples were selected among youth. For the purpose of getting an insight and a good generalization, five constructs were theoretically formulated and hypothesized to address the research question. The results revealed that the variables were moderately correlated and significantly related for youth involvement in Youth Program.